2022
DOI: 10.1186/s13045-022-01233-3
|View full text |Cite
|
Sign up to set email alerts
|

Serologic response following SARS-COV2 vaccination in patients with cancer: a systematic review and meta-analysis

Abstract: Purpose Patients with cancer have an increased risk of coronavirus disease 2019 (COVID-19) and an attenuated responses to various vaccines. This meta-analysis aims to assess the serologic response to COVID-19 vaccination in patients with cancer. Methods Electronic databases were systematically searched on August 1, 2021 for studies that reported the serologic response to COVID-19 vaccine in cancer patients. Random effects models were used to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 52 publications
1
29
1
Order By: Relevance
“…Some populations have been shown to have higher susceptibility to this disease, including those with malignancies. Immunodeficiency in individuals with malignancies can be caused by the properties of the disease itself and by the effects of the radiation or chemotherapy ( 10 ). A study with 507,307 patients with COVID-19 showed that cancer patients who also received anticancer treatment within 3 months before the diagnosis of COVID-19 had an increased risk of hospitalization, admission to intensive care units, and death ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some populations have been shown to have higher susceptibility to this disease, including those with malignancies. Immunodeficiency in individuals with malignancies can be caused by the properties of the disease itself and by the effects of the radiation or chemotherapy ( 10 ). A study with 507,307 patients with COVID-19 showed that cancer patients who also received anticancer treatment within 3 months before the diagnosis of COVID-19 had an increased risk of hospitalization, admission to intensive care units, and death ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 15 ) and Sakuraba et al. ( 10 ). However, due to the small number of included studies and the wide confidence interval, the results might seem insignificant.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The COVID-19 vaccine systematic reviews predominantly used seroconversion as a marker for vaccine efficacy. In general, the studies showed that patients with chronic kidney failure on dialysis (not requiring organ transplantation) [ 10 , 11 , 12 ], immune-mediated inflammatory diseases [ 13 , 14 , 15 , 16 ], and solid tumors [ 17 ] had seroconversion rates that were high and similar to healthy controls (seroconversion rates among patients ranged from about 83% to 97%). In contrast, patients with receipt of anti-CD20 therapy [ 18 ] and solid organ transplants [ 11 , 19 , 20 ] (thus requiring anti-rejection immunosuppression) had markedly low vaccine seroconversion rates (rates ranged from about 26% to 45% after two vaccine doses).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] A recently published metaanalysis put the pooled proportion of patients achieving a serologic response after a second dose of the vaccine around 87% but was sure to acknowledge that patients with HMs are less likely to mount a response as compared with patients with solid organ cancers (63.7% vs 94.9%), likely due to the type of HM and/or current treatments. 10,11 Another large study, the CAPTURE study, showed that in patients with HMs, neutralizing antibodies, our current indication of vaccine effectiveness, are significantly reduced, and this appears to hold true with the most recent variant of concern (VOC), Omicron. 1,4,12, In the summer of 2021, when the "booster dose" was authorized under the United States Food and Drug Administration (FDA) Emergency Use Authorization (EUA), cancer patients were rightly prioritized for this third shot (3V).…”
Section: Introductionmentioning
confidence: 99%